Socializing The Benefits Of Telemedicine In Maternity Nursing To Pregnant Women And Healthcare Workers In Tuban Regency - Qoyimah, Ilmiatus; Safaah, Nurus; Ilmiatus (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Telemedicine has become a vital tool in delivering healthcare services, particularly in rural areas with limited access. This study aims to socialize the benefits of telemedicine to pregnant women and healthcare workers in Tuban Regency, focusing on its potential in maternity care. A socialization program was conducted with 50 participants, including 20 healthcare workers and 30 pregnant women. The program included presentations, demonstrations, and practical training on telemedicine use for maternity care. Knowledge and usage were evaluated before and after the program through surveys. The socialization resulted in a significant knowledge increase, with 80% of pregnant women and 90% of healthcare workers reporting improved understanding of telemedicine. Furthermore, 65% of pregnant women and 75% of healthcare workers began utilizing telemedicine for consultations. However, 28% of participants faced technical challenges, such as internet connectivity and device limitations. Additionally, 72% of participants expressed interest in further training. The program successfully enhanced knowledge and confidence in using telemedicine. Despite technical barriers, adoption rates were encouraging, underscoring the need for ongoing training and enhanced digital infrastructure to facilitate the broader adoption of telemedicine in rural healthcare. Socializing telemedicine in Tuban has proven effective in raising awareness and encouraging adoption. However, addressing technical barriers and providing ongoing education are essential for maximizing its impact on maternity care.